2022
DOI: 10.3390/insects13050405
|View full text |Cite
|
Sign up to set email alerts
|

Wing Phenotypic Variation among Stomoxys calcitrans (Diptera: Muscidae) Populations in Thailand

Abstract: Stomoxys calcitrans (Linnaeus, 1758) (Diptera: Muscidae) is a cosmopolitan hematophagous ectoparasite of veterinary and medical importance. It is an important mechanical vector of several animal pathogens and can cause significant economic losses. However, the morphological variation of this species remains unknown. This study aimed to investigate the phenotypic variation in the wing size and shape of S. calcitrans populations in Thailand based on a landmark-based geometric morphometric approach. Specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…They used 10 landmark positions on the wing for distinguishing morphologically similar species of Stomoxys flies ( S. pullus , S. uruma , and S. indicus ). Subsequently, it was evidenced that these landmark positions can be used to discriminate individuals among the other Stomoxys flies, namely S. bengalensis , S. calcitrans , and S. sitiens ( Changbunjong et al, 2023 ) and can also be used to explore the phenotypic variation of S. calcitrans ( Chaiphongpachara et al, 2022b ) as well as the sexual dimorphism of H. aberrans ( Changbunjong et al, 2020 ). Therefore, we also used the same landmark positions for the GM analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They used 10 landmark positions on the wing for distinguishing morphologically similar species of Stomoxys flies ( S. pullus , S. uruma , and S. indicus ). Subsequently, it was evidenced that these landmark positions can be used to discriminate individuals among the other Stomoxys flies, namely S. bengalensis , S. calcitrans , and S. sitiens ( Changbunjong et al, 2023 ) and can also be used to explore the phenotypic variation of S. calcitrans ( Chaiphongpachara et al, 2022b ) as well as the sexual dimorphism of H. aberrans ( Changbunjong et al, 2020 ). Therefore, we also used the same landmark positions for the GM analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we do not suggest using the wing size to distinguish these flies if the sex of the flies is unknown. In fact, it has also been shown that the wing size is unsuitable for the differentiation of insect species because it is frequently influenced by environmental factors ( Jirakanjanakit et al, 2007 ; Morales Vargas et al, 2010 ; Baleba et al, 2019 ; Phanitchat et al, 2019 ; Chaiphongpachara et al, 2022b ; Chaiphongpachara et al, 2022c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WGM is largely developed in several vectors families like as Culicidae [see review of Lorentz et al ( 29 )] to explore intraspecific variations among mosquito populations or to research interspecific variation, to study in sexual dimorphism, plasticity and deviation, to detection of parasites and to characterize laboratory strain. This technique was used to study the intra specific variations in Glossinidae ( 30 ), Muscidae ( 31 ), Psychodiae ( 28 , 32 , 33 ), Reduviidae ( 34 ) and Tabanidae ( 35 , 36 ) and to show inter specific variations in Muscidae ( 37 ). The landmark-based WGM analysis of Culicoides wings has proven to be a valuable tool for interspecific discrimination ( 38–42 ), C. circumscriptus intersexes specimens ( 43 ), sexual dimorphism ( 44 ) and geographic variations ( 45 ).…”
Section: Introductionmentioning
confidence: 99%